The Gambia : Poverty Reduction Strategy Paper; Annual Progress Report. (IMF Staff Country Reports; Country Report ;, 2006)
This Annual Progress Report focuses on The Gambia's Poverty Reduction Strategy Paper (PRSP). It provides information and analysis regarding the achievements and shortfalls experienced between July 2002 and December 2003 with respect to the poverty targets, priority public actions, and the monitoring and evaluation systems put in place for the PRSP/Strategy for poverty alleviation II (SPA II). The report highlights important changes necessary in the strategy as appropriate in light of implementation experiences to date, changes in exogenous factors, and new data and analysis regarding poverty and its dimensions.